LEARNING MODEL OF CITIZENSHIP BASED ON CREATIVE DEVELOPMENT - M. Andriana Ghafar, Nani Nur’aeni & (Department of Civic Education, 2014)
Creative development based learning, theoretically, is the conditioning of highest cognitive learning to achieve curricular purposes of CivicÂ Education subject.Â Research findings that conducted in senior high school level, showed four models which support the creative devevelopment approach, i.e. research based learning, goods based learning, product based learning, information synthetizing and facts discovery based learning. The learning process developed conctructivistic, contextualan dinquire.